NEWSPAPERS IN GERMAN ABOUT THE ACTIVITIES OF SHEMSI PASHA BIŠEVAC IN THE KOSOVO VILAJET (Heritage, 2023)
Since Abdul Hamid's accession to the throne, the Ottoman Empire was sinking into a deep crisis that affected all segments of society. The weakening of the state was influenced by numerous factors, primarily financial, political, military and diplomatic, which led to territorial losses. Territorial and demographic losses were reflected in the reduction of income and led to greater decline of the state. Such a situation created constant dissatisfaction both among conservative circles, disappointed with the introduction of novelties under pressure from foreigners, and among liberals who were bothered by the autocratic rule of Sultan Abdul Hamid. Additional dissatisfaction was also present due to the unresolved national question, which caused frequent movements of numerous nations within the Empire.            The accelerated collapse of the Ottoman Empire was noticeable in all its parts. In the Kosovo vilajet, as part of the Ottoman state, the first decade of the 20th century was marked by numerous movements of the dissatisfied population. The reasons for the outbreak of rebellions were various: bad economic situation, introduction of new taxes, attempts to collect old ones, loss of privileges, foreign influences, propaganda, etc. The situation in the Kosovo vilajet was further complicated by the behavior of the Albanians, who were exposed to the propaganda of the Ottoman state, which called them the defenders of the Empire. On the other hand, the great powers had a significant foreign influence, first of all, Austria-Hungary, from where the idea of independence was increasingly imposed on them.        The Albanian rebellions most often were of a political character, but there were also those whose background was of a social nature. Everyday movements were also caused by the intolerance of the Albanians towards the Serbian population.            The Ottoman authorities rarely took adequate measures against disgruntled rebels, except in cases when the movements threatened to take on larger proportions. In such circumstances, they sent detachments of soldiers, with the aim of appeasing the rebels as painlessly as possible. The degree of military involvement depended on the size of the movement. Larger rebellions, in addition to the army, also required the engagement of officers, capable and ready to tackle the problem. One of them who stood out for his willingness, energy and perseverance was Shemsi Pasha Biševac.            He was born in the Rožaj area, in the village of Biševo in 1846. He received his education in Constantinople, and built his military career throughout the Ottoman Empire. He first stayed in Bosnia in 1866, where he received the rank of sergeant, then lieutenant and captain. He participated in the Russo-Turkish war of 1877-1878, in which he was also wounded. Military involvement, determination and experience were his main recommendation to the Sultan Abdul Hamid. Thanks to his participation in numerous actions of the Turkish army, Shemsi Pasha was promoted, and in September 1901 he was appointed commander of the 18th Nizam Division in Mitrovica. At the beginning of the 20th century, he was an eyewitness and active participant in the events marked by lawlessness and disorder in the Kosovo vilayet.The Porte, wishing to restore order, sent Shemsi Pasha to those regions. He arrived in Kosovo vilajet on April 16, 1900. According to the German-language press, due to his attitude towards the state, his conservative views, but also his energy and perseverance to restore order in the rebellious regions, he caused dissatisfaction among the Albanians, who were used to privileges, disrespect for the law and were ready to resist reforms. He was killed on July 7, 1908 in Bitola.
Keywords: Shemsi Pasha, Ottoman Empire, Kosovo Vilajet, press, rebellions